Myocardial reserve in patients with myocardial infarction: the role of clinical and functional parameters in its assessment - A. P. Ivanov; I. A. Elgardt; V. A. Leontyev (Российский кардиологический журнал, 2005)
To identify the most informative characteristics of myocardial reserve (MR) inpatients with myocardial infarction (MI), the authors compared clinical symptoms of heart failure (HF), systolic and diastolic myocardial function, and left ventricular (LV) remodeling parameters. Data from 220 patients demonstrated that low LV ejection fraction was a significant predictor only for high HF functional class (FC). Diastolic dysfunction (DD) was typical for all HFFC, and restrictive type of heart filling was associated with HF FC III-IV. Concentric LV hypertrophy, as well as DD, was observed in all HF FC. Prevalence of eccentric hypertrophy significantly increased from 5,1% in FC 1to 98,7% in FC IV. This characterizes the latter process as most typical for MR decrease in MI patients. The authors propose a new gradation for MR decline, and discuss correlations among HF FC, DD, myocardial contractility, and myocardial remodeling.